A new system for multiplexed mosaic analysis of gene function in the mouse - Hongchen Cai; Monte M. Winslow (Cell Reports: Methods, 2022)
In a recent issue of Cell, Liu et al. present an innovative mouse model system in which Cre/lox stochastically turns on transgenic expression of one out of up to 100 sgRNAs in somatic cells, creating genetic mosaicism that enables the multiplexed assessment of gene function in vivo.